A broad-range survey of ticks from livestock in Northern Xinjiang: changes in tick distribution and the isolation of Borrelia burgdorferi sensu stricto. Issue 1 (December 2015) - Wang, Yuan-Zhi; Mu, Lu-Meng; Zhang, Ke; Yang, Mei-Hua; Zhang, Lin; Du, Jing-Yun; Liu, Zhi-Qiang; Li, Yong-Xiang; Lu, Wei-Hua; Chen, Chuang-Fu; Wang, Yan; Chen, Rong-Gui; et al.
Abstract Background Borreliosis is highly prevalent in Xinjiang Uygur Autonomous Region, China. However, little is known about the presence ofBorrelia pathogens in tick species in this region, in additionBorrelia pathogens have not been isolated from domestic animals. Methods We collected adult ticks from domestic animals at 19 sampling sites in 14 counties in northern Xinjiang from 2012 to 2014. Ticks were identified to species by morphology and were molecularly analysed by sequences of mitochondrial16S rDNA gene; 4–8 ticks of each species at every sampling site were sequenced. 112 live adult ticks were selected for each species in every county, and were used to cultureBorrelia pathogens; the genotypes were then determined by sequences of the5S-23S rRNA intergenic spacer and the outer surface protein A (ospA ) gene. Results A total of 5257 adult ticks, belonging to four genera and seven species, were collected. Compared with three decades ago, the abundance of the five common tick species during the peak ixodid tick season has changed. Certain tick species, such asRhipicephalus turanicus (Rh. turanicus ), was found at Jimusaer, Yining, Fukang, and Chabuchaer Counties for the first time. Additionally, the sequence analyses showed that theHyalomma asiaticum (Hy. asiaticum ), Haemaphysalis punctata (Ha. punctata ), andDermacentor marginatus (D. marginatus ) that were collected from different sampling sites (≥3 sites) shared identical16S rDNA sequences respectively. For the tick species that were collected from the same county, such asHy. asiaticum from Shihezi County andRh. turanicus from Yining County, their 16SrDNA sequences showed genetic diversity. In addition, sixteenBorrelia isolates were found inHy. asiaticum, Ha. punctata, D. marginatus andRh. turanicus, which infested cattle, sheep, horse and camel in Yining, Chabuchaer, Shihezi and Shawan Counties. All of the isolates were genetically identified asB. Burgdorferi sensu stricto . Conclusions Warmer and wetter climate may have contributed to the altered distribution and abundance of the five most common ticks in northern Xinjiang. The genetic analyses showed that certain tick species, such asHy. asiaticum orRh. turanicus, exhibit genetic commonness or diversity. Additionally, this study is the first to isolateB. burgdorferi sensu stricto inHy. asiaticum asiaticum, H. punctata, D. nuttalli andD. marginatus ticks from domestic animals. These ticks may transmit borreliosis among livestock.